Mortalidad y reclutamiento de árboles en un bosque secundario tardío del valle de Chanchamayo, Perú - Giacomotti Tuezta,José (2018)
The present study evaluated the parameters of mortality and recruitment of the forest dynamics at a permanent plot of one hectare located in a late secondary forest area, at 1158 m above the sea level (masl) in the premontane stratum of the Chanchamayo Valley, Department of Junín, in the central jungle of Peru. All individuals with a diameter at breast height (DBH) greater than or equal to 10cm were recorded, after an intercensal period of 3.7 years. The establishment and the first measurement of the plot was performed in 2010, registering a population of 512 individuals. The remeasurement was carried out in 2014, finding 35 dead individuals and 59 recruits, having as final population 536 individuals. The species that presented more dead individuals were Trophis caucana (Pittier) C.C.Berg (19 individuals), Coussapoa villosa Poepp. & Endl. (5 individuals), Cupania cinerea Poepp. (3 individuals), Cecropia membranacea Trécul (2 individuals) and Pseudobombax munguba (Mart.) Dugand (2 individuals). The species that presented the highest number of recruits were Trophis caucana (30 recruits), Guarea guidonia (L.) Sleumer (5 recruits), Bunchosia armeniaca (Cav.) DC. (3 recruits) and Trema micrantha(L.) Blume (3 recruits). Recording the annual mortality rate of 1.91% and the annual recruitment rate of 3.15%. The halflife and duplication time for this forest were calculated at 36 years and 22 years respectively. Based on the results, the conclusion is that the forest presents a moderately high dynamics and is increasing its arboreal density.